Animal attendance at M‐44 sodium cyanide ejector sites for coyotes - John A. Shivik; Lauren Mastro; Julie K. Young (Wildlife Society Bulletin)
ABSTRACT Sodium cyanide (NaCN) ejectors for coyotes (Canis latrans), known as M‐44s, are used in many parts of the United States for lethally removing coyotes to protect livestock or other resources. Quantifying selectivity of current devices in killing target and non‐target species is important to users and provides a baseline for future development of more effective and selective techniques. We used motion‐activated cameras to monitor M‐44 locations for coyote and other species visitations to the sites. Because camera presence potentially influences coyote behavior, we first compared activation of M‐44s at paired sites where cameras were and were not present. Coyotes activated M‐44s sites with cameras (n = 17) similarly to sites without cameras (n = 19). During 832 site‐days of observation, coyotes visited M‐44 sites 29 times, and 18 other species visited 1,597 times. The mean visitation ratio for non‐coyotes to coyotes was 2.8:1 at the M‐44 locations monitored (n = 22). Non‐coyotes were much less likely to touch the devices with their noses or mouths than were coyotes (0.24:1). No non‐canid activated an M‐44, suggesting very high selectivity toward killing canid species. Published 2013. This article is a U.S. Government work and is in the public domain in the USA.